Representation of Concept MYTH in Austrian Literature (Works of Elias Canetti and Barbara Frischmuth) - A. G. Barova; L. V. Trofimova (Научный диалог)
This article explores the works of Austrian writers Elias Canetti (1905—1994) including the novel “Auto-da-Fé” (“Die Blendung”, 1935) and the autobiographical book “The Tongue Set Free: Remembrance of a European Childhood” (“Die gerettete Zunge. Geschichte einer Jugend”, 1977), as well as Barbara Frischmuth (born 1941) with works such as “Queen of the Animals” (“Herrin der Tiere”, 1986), “Beyond Measure” (“Über die Verhältnisse”, 1987), and “Children to Each Other” (“Einander Kind”, 1990) within the context of 20th-century Austrian literature. The article identifies and analyzes mythological images present in these works, focusing on the concept of ‘personal myth’ (interpreted by Elias Canetti as ‘Privatmythos’). Through a genre-based analysis, the article delves into the artistic realization of the authors’ personal myths and the motives behind myth-making. It is established that the personal myth encompasses aspects of both the “mythical” and the “mythological”. The authors suggest a distinction between these terms, which have ambiguous interpretations. It is argued that Canetti viewed the ‘personal myth’ as an individual’s unique dream or fixation, representing their aspirations. Canetti’s autobiography allows for a synthesis of existing and constructed facts. In her “Demeter Trilogy”, Barbara Frischmuth constructs a comprehensive worldview where archaic mythology interacts with modernity, offering insights into contemporary cultural realities.